Anxiety during pregnancy and at three months postpartum: prevalence, variations and associated factors in a cohort of nulliparous women - RAFFERTY, LOUISE ANN (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2019)
Anxiety during pregnancy and at three months postpartum: prevalence, variations and associated factors in a cohort of nulliparous women. Background. As an adaptive emotion, anxiety enhances reactions to challenging life experiences. However, anxiety can become overwhelming and debilitating. In two longitudinal studies, the prevalence of anxiety ranged from 12.2% to 14.6% in pregnancy, decreasing to 4.8% and 8.1% respectively at three months postpartum. However, the prevalence varies considerably depending on the definition of anxiety, the measurement scales used, the population studied, the time of assessment and the study's attrition rates. There is a dearth of information available on the prevalence of perinatal anxiety amongst women in Ireland. Objectives The objectives were to: i) determine the prevalence of anxiety in first-time mothers in pregnancy and at three months postpartum; ii) explore the changes in prevalence between pregnancy and three months postpartum; (iii) identify the existence of the co-morbidities of depression and stress, at both time points, and (iv) to report the factors associated with anxiety in pregnancy and at three months postpartum. Methods The cohort of women and data for this study were identified from the longitudinal prospective cohort Maternal health And Maternal Morbidity in Ireland study (MAMMI study). Prevalence of anxiety was determined using two measurement scales, the anxiety items in the Edinburgh Postnatal Depression Scale (EPDS 3A), the anxiety subscale within the Depression, Anxiety and Stress Scale 21 (DASS 21 anxiety subscale), and a single item statement from a sample of 1668 women who completed self-administered surveys at two time points. A range of sociodemographic and clinical factors, identified from the surveys and women's hospital records, were assessed for associations with anxiety. Results Prevalence of anxiety in pregnancy was 9.3%, 15.1% and 26.4%, depending on the measurement scales and the cut-off scores used. At three months postpartum, prevalence decreased from 9.3% to 8.7% and from 26.4% to 24.6%, measured using EPDS 3A cut-off scores ≥6 and ≥4 respectfully, and from 15.1% to 8.6% according to the DASS 21 anxiety subscale. According to the single item statement, prevalence increased from 12.4% in pregnancy to 28.1% at three months postpartum. Prevalence of anxiety was greater than depression or stress in pregnancy however, it was lower postpartum. Factors significantly associated with anxiety using both the DASS 21 and the EPDS 3A in pregnancy included country of birth, educational level and smoking. Postpartum, educational level, relationship problems with husband/partner, fear of any partner, a need for more emotional support and breastfeeding were significantly associated with anxiety according to both scales. At both time points and for both scales the single item anxiety statement for experiences of anxiety in a life time was significantly associated with anxiety. Conclusion Findings show that prevalence of anxiety in the same cohort of women varied widely at and between the two time points; in pregnancy and at three months postpartum. While the prevalence of anxiety decreased between the two time points according to the measurement scales used, the decrease was greatest using the DASS 21 which has yet to be validated for use in pregnancy. There was less of a decrease in prevalence, according to the EPDS 3A at both time points and according to both cut-off scores. On the other hand, prevalence increased between pregnancy and three months postpartum according to the single statement. Nonetheless, it was found that a considerable proportion of first time mothers report anxiety in pregnancy and at three months postpartum irrespective of the measurement scale or statement used.
APPROVED
Keywords: Anxiety. Perinatal Anxiety. Maternal Anxiety. Antenatal anxiety. Prenatal anxiety. Postnatal anxiety. Postpartum anxiety. EPDS. EPDS 3A. Edinburgh Postnatal Depression Scale. DASS 21. Depression, Anxiety and Stress Scale.